Sanksi Pidana Untuk Pemerasan dan Ancaman Online Cybersex: Analisis Putusan Nomor: 229/Pid.Sus/2021/PN.Prp Dalam Perspektif Hukum Islam - Butar, Rini Andriani; Ramadani (JOM, 2024)
This study analyzes the criminal sanctions applied in cases of extortion and online threats related to cybersex, with a focus on Decision Number: 229/Pid.Sus/2021/PN.Prp. This study aims to evaluate the conformity of the decision with Islamic legal principles. The method used is a normative juridical method with a case approach. Data were collected through literature studies that included primary and secondary legal materials. The results of the study show that the judge in making the verdict has considered the evidence submitted as well as the aspects of justice and usefulness in accordance with the Criminal Code (KUHP) and Law Number 19 of 2016 concerning Information and Electronic Transactions (UU ITE). However, from the perspective of Islamic law, some important elements such as the application of hudud and qisas in similar crime cases require further consideration. Islamic law emphasizes the fair enforcement of the law and the prevention of moral damage in society, so this analysis also evaluates how the criminal sanctions imposed are in harmony with these principles